P60 Uptake and Quality of Health Surveillance for Occupational Asthma in the UK. (12th November 2015) - Fishwick, D; Sen, D; Barker, P; Codling, A; Fox, D; Naylor, S
Abstract : Introduction: Statutory periodic health surveillance (HS) of workers can identify early cases of occupational asthma. Information about its uptake in the UK, and its content when carried out, are lacking. Methods: A telephone survey of employers, and their occupational health professionals, was carried out in three sectors with the potential for producing exposures, which may result in the development of occupational asthma (bakeries, wood working, motor vehicle repair). Results: 457 organisations participated (31% response rate); 77% employed less than 10 people, 17% between 10 and 50 and 6% more than 50. Risk assessments were common (67%) and 14% carried out any form of occupational asthma HS, rising to 19% if only organisations reporting asthma hazards and risks were considered. HS was carried out by both in-house (31%) and external providers (69%). Organisational policies were often used to define surveillance approaches (80%), but shared with the occupational health provider only in one third of cases. Occupational health providers described considerable variation in practice, with differing approaches seen for information sharing and workplace visits. Record keeping was universal, but worker-held records were not reported. Health surveillance tools, such as a questionnaire, were generally developed in-house. Lung function was commonly measured, but only limited interpretation was evident. The referral of workers to local specialist respiratory services was variable. Conclusions: This study has provided new insights into the real world of health surveillance for occupational asthma in the UK. We consider that future work could and should define more practical, evidence based and simple approaches to HS, by working with the end users to develop interventions that meet their needs. This will ensure maximal uptake of high quality HS approaches and consistency.